Infrared thermography of swine body surface temperatures and associated rectal temperatures during an acute respiratory disease challenge - J A Loughmiller; M F Spire; B W Fenwick; S Hogge; J Foster; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
An acute Actinobacillus pleuropneumonia challenge was used to study changes in rectal and radiant surface temperatures over 18 h. From 3.5 to 15 h after challenge, rectal temperatures were elevated in challenged pigs compared to nonchallenged controls. From 6 through 18 h after challenge, infrared surface temperature was higher for challenged pigs versus control nonchallenged pigs. Correlation coefficient analysis indicated that surface temperature and rectal temperature were moderately correlated. These results indicate that infrared thermography will detect changes in body surface temperature associated with the acute phase febrile response and has potential as a diagnostic tool for assessing systemic changes in radiant heat production.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Fever; Infrared thermography; Rectal temperature